Skenario Pengembangan Produksi Lapangan “NATA” dengan Software Integrated Production Modelling - Lia Yunita; Heru Danardatu; Endro Tegar Prakoso (LPPM Institut Teknologi Petroleum Balongan, 2025)
Integrated production modeling (IPM) is a software for modeling oil and gas production systems from reservoirs, wells and surface networks. IPM consists of GAP, PROSPER, MBAL, PVTP, REVEAL and RESPLVE. The purpose of the study is to plan the development scenario of the